2009
DOI: 10.5005/jp-journals-10009-1024
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Pregnancies with Increased Nuchal Translucency and Normal Karyotype

Abstract: The aim of this study was to examine the prevalence of major and minor anomalies according to the increase of NT thickness. Methods: This is a long-term retrospective study in which singleton gestations of euploid fetuses with increased NT were analyzed. NT measurement was performed in the first trimester examination according to the criteria of fetal medicine foundation (FMF) when the fetal crown-rump length (CRL) was 45 to 84 mm. The cases were followed up from 1 to 5 years postpartum to assess the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
2
9
1
Order By: Relevance
“…According to the results, the strongest correlation (60%) was observed between the diagnosis of a prenatal congenital heart defect and the thickness of 2.5 to 3.4 mm. The present results were consistent with the f indings of Orosz (2009), in which the prevalence of heart defects increased with NT enhancement. In line with our results, Saldanha (2009) reported that the prenatal heart defects and postnatal abnormalities are related to the NT thickness.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…According to the results, the strongest correlation (60%) was observed between the diagnosis of a prenatal congenital heart defect and the thickness of 2.5 to 3.4 mm. The present results were consistent with the f indings of Orosz (2009), in which the prevalence of heart defects increased with NT enhancement. In line with our results, Saldanha (2009) reported that the prenatal heart defects and postnatal abnormalities are related to the NT thickness.…”
supporting
confidence: 92%
“…A congenital heart defect is the most frequent congenital malformation affecting 4% to 8% infants which is one of the main responsive factors for neonatal deaths in the f irst year of their life (Haak & van Vugt, 2003). Half of these malformations are asymptotes minor def icits and the other half are considered as major (Orosz , 2009;Galindo , 2003). It was revealed that prenatal diagnosis can be a very helpful and even life-saving option in case of def inite fetal heart def icits and other structural abnormalities (Becker & Wegner, 2006 approved as a sensitive parameter for the screening of chromosomal and heart defects in both chromosomally normal and abnormal fetuses (Orosz ., 2009;Galindo ., 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lindsey et al, (2006) concluded 20 % of adverse pregnancy outcome in increased nuchal translucency euploid fetuses 15 . The overall rate of adverse pregnancy outcome was proportional to the degree of NT enlargement, ranging from 1.9 % to 64.7 % such as Bilardo et al, (2007) 20 . This difference can be due to 5 year postnatal follow up of cases.…”
Section: Euploid Fetuses With Increased Nuchal Translucency In Prenatmentioning
confidence: 99%
“…60,61 Since the 1990s, extensive studies have established that euploid fetuses with increased nuchal translucency (NT) have a higher risk for a wide range of fetal structural defects, for specific genetic syndromes, and especially for congenital heart defects (CHD). 62,63 Severe CHDs with high probability of detection by EFE: D-and L-transposition of the great arteries (D-TGA, L-TGA) hypoplastic left heart syndrome (HLHS) based on aortic and mitral valve atresia or severe stenosis; atrioventricular septal defect (AVSD); double outlet right ventricle (DORV); common arterial trunk (CAT); double inlet left ventricle (DILV); tricuspid atresia (TA); mitral atresia (MA); pulmonary atresia (PA); heterotaxy syndromes; total anomalous pulmonary venous return (TAPVR); large ventricular septal defects (VSD).…”
Section: Early Fetal Echocardiography At the Time Of 11+0 To 13+6 Weeksmentioning
confidence: 99%